NORMAL CHILDBIRTH OR CESAREAN? FACTORS AFFECTING THE CHOICE OF PREGNANCY - Susanne Pinheiro Costa e Silva; Renata de Carvalho Gomes Prates; Bruna Queiroz Armentano Campelo (Universidade Federal de Santa Maria, 2014)
http://dx.doi.org/10.5902/217976928861 Aim: to know the factors that influence the decision of the parturition mode of pregnant women attending Juazeiro-Bahia, Health Unit. Method: qualitative research if character exploratory-descriptive, developed with pregnant women followed in the Family Health Unit of Juazeiro-BA, conducted between March and June, 2010. Twelve pregnant women, with aged over 18 years, participated in the semi-structured interviews. For the categorization of the material, it was used content analysis. Results: most of them opted for normal parturition because has a rapid recovery. Previous experience influenced in parturition choice, whether herself or others. Among the influences reported, stood his mother, health professionals and the media. Noted that the information given in prenatal were unsatisfactory. Final Thoughts: it emphasizes the importance of access to a care quality prenatal, with actions that provide safe choices, clarifying doubts and reassures of the future mother, reassuring her to the time of parturition.